2013
DOI: 10.1002/mar.20659
|View full text |Cite
|
Sign up to set email alerts
|

Consumption‐Focused Self‐Expression Word of Mouth: A New Scale and Its Role in Consumer Research

Abstract: This research represents the first systematic empirical examination of the motivation to spread word of mouth about consumption activities in order to self‐express, a phenomenon that has been observed in both the academic literature and the popular press. Consumption‐focused self‐expression is a motivation to engage in word‐of‐mouth communication that is distinct from other word‐of‐mouth motivations that have been discussed in the literature. This work defines consumption‐focused self‐expression word of mouth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 86 publications
(125 reference statements)
0
77
2
1
Order By: Relevance
“…However, although numerous prior studies demonstrate how consumers use brands to communicate the type of person they are to others (e.g. Belk, 1988;Moutinho et al, 2007;O'Cass, 2000), there is a dearth of research investigating whether the desire for self-expressive brands may serve as a motivation to spread WOM (Saenger et al, 2013). A study of brand love has suggested a positive relationship between self-expressive brands and WOM (Carroll and Ahuvia, 2006), but this relationship has remained largely unexplored in the academic literature.…”
Section: H7: There Is a Positive Relationship Between Brand Tribalismmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although numerous prior studies demonstrate how consumers use brands to communicate the type of person they are to others (e.g. Belk, 1988;Moutinho et al, 2007;O'Cass, 2000), there is a dearth of research investigating whether the desire for self-expressive brands may serve as a motivation to spread WOM (Saenger et al, 2013). A study of brand love has suggested a positive relationship between self-expressive brands and WOM (Carroll and Ahuvia, 2006), but this relationship has remained largely unexplored in the academic literature.…”
Section: H7: There Is a Positive Relationship Between Brand Tribalismmentioning
confidence: 99%
“…WOM is defined as "the informal communication that occurs between private parties when there are evaluations of goods and services" (Anderson, 1998 p. 6). WOM is of importance for this study as previous research shows that consumers like to discuss and exchange information about the brands they consume (Gabrielli et al, 2013;Saenger et al, 2013;Veloutsou and Moutinho, 2009). In particular, talking about brands with others helps consumers both express and construct their selfconcept (Carroll and Ahuvia, 2006).…”
Section: H7: There Is a Positive Relationship Between Brand Tribalismmentioning
confidence: 99%
“…While they like new technology (Atkinson, 2013;Barnes & Pressey, 2012) and acknowledge the relative advantage of online shopping in terms of excitement and the convenience of a delivery service (Pechtl, 2003) as well as the ability to hunt for deals (Boon, 2013), they are less likely to use or adopt online banking (Lassar, Manolis, & Lassar, 2005), more strongly disapprove of the missing touch-and-feel experience and have stronger doubts about data protection (Pechtl, 2003). Research also suggests that the market maven scale is not the best predictor of online word-ofmouth communications (Saenger et al, 2013). These findings lead to the next hypothesis:…”
Section: Consumer Information Sourcesmentioning
confidence: 94%
“…Mavens even pass on established that people use brands and products to communicate their sense of identity (Belk, 1988;Twigg, 2007), so perhaps in a similar way people use consumption-related information as a way of expressing themselves (Saenger, Thomas, & Johnson, 2013). Finally, it is well established that some people take extreme pleasure from shopping as a leisure activity.…”
Section: Introductionmentioning
confidence: 99%
“…Within this scope they can transfer the products and brands they choose to their selves by ascribing them a special meaning. The researchers on the subject conclude that the performed consumption activities support individuals to communicate with their selves and construction of self [27]. Escalas and Bettman [28] claim that consumers use products and brands to create and image of the self and present this image to others by creating a bond between self and brand [29] express that through the products they possess, individuals can develop social identity as well.…”
Section: Construction Of Self Through Consumptionmentioning
confidence: 99%